Financial concerns and symptom distress among psychiatric outpatients. Issue 3 (17th September 2018) - Kealy, David; Spidel, Alicia; Sandhu, Sharan; Kim, Dan; Izbicki, Andrew
Abstract : Purpose: While epidemiological studies have linked economic hardship and financial difficulties with psychological distress and suicide, investigation of financial concerns among users of public mental health services has been limited. Moreover, empirical data regarding a relationship between financial difficulties and mental health symptoms are lacking. The purpose of this paper is to examine the prevalence of financial difficulties among patients attending community mental health clinics, and to examine the relationship between such difficulties and psychological distress and suicidality. Design/methodology/approach: Participants attending three community mental health clinics in British Columbia, Canada provided demographic information, including annual income, and completed brief measures of personal financial management, psychological distress and suicidal behavior. Findings: Although more than half of participants reported good-to-excellent ability to pay their bills on time, nearly half indicated poor long-range saving and financial planning. Lower annual income was directly related to suicidality. Financial management difficulties were associated with psychological distress, and were significantly related to suicidality after controlling for the effects of income and psychological distress. Originality/value: The findings highlight the need for attention to distress and suicidality as potential sequelae of financial management difficulties, and carry implications for further research, clinical intervention and social policy. The findings confirm the need to address financial needs and money management abilities among users of public mental health services.